“A STUDY ON STRESS MANAGEMENT AT MOTHERSON AUTMOTIVE TECHNOLOGIES & ENGINEERING CHENNAI” - Ms Magdalene Peter (International Journal of Modern Agriculture, 2020)
Stress produces numerous symptoms which vary according to persons, situations, and severity. These can include physical health decline as well as depression. The process of stress management is named as one of the keys to a happy and successful life in modern society. Although life provides numerous demands that can prove difficult to handle, stress management provides a number of ways to manage anxiety and maintain overall well-being. Despite stress often being thought of as a subjective experience, levels of stress are readily measureable using various physiological tests, similar to those used in polygraphs. Many practical stress management techniques are available, some for use by health practitioners and others for self-help, which may help an individual to reduce stress, provide positive feelings of being in control of one’s life and promote general well-being. The effectiveness of the different stress management techniques can be difficult to assess, as few of them have received significant attention from researchers. Consequently, the amount and quality of evidence for the various techniques varies widely. Some are accepted as effective treatments for use in psychotherapy, whilst others with less evidence favoring them are considered alternative therapies. Many professional organizations exist to promote and provide training in conventional or alternative therapies.